(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The article focuses on the material culture of the left bank of the Amu Darya, the history of research and their historical and written sources, which are the sacred lands between Jayhun and Sayhun, formed between two rivers that are the centers of civilization in our history.